Efektivitas Tunjangan Kinerja Daerah Pegawai Badan Kepegawaian Daerah Provinsi Sulawesi Utara - Worotitjan, Flora . (JURNAL ILMIAH SOCIETY, 2015)
Allowance for employee performance based on efforts to increase the motivation and discipline as well as boost productivity Civil Servants in the scope of the Provincial Government of North Sulawesi . This study aimed to analyze the effectiveness of regional performance benefits of employees in the Civil Service Agency of North Sulawesi Province . By using a qualitative design , the study concluded that administration of performance-based performance benefits of civil servants in the Regional Employment Board has not efekif make employees have the ability to adjust , resulting in job performance and job satisfaction . The determination of the amount of allowances to her performance based on workload analysis not tingkaan positions and classes , tailored to the competency -based reward system .Â Keywords : Effectiveness, Performance Benefits, Employee.